Chemical Quality (Water Content, Protein, Fiber) and Organoleptic Properties of Chicken Nuggets with Addition of Vegetables - Nurhayati, Nurhayati; Parwati, Meisy Rian; Khotimah, Khusnul; Handoko, Heru; Nelwida, Nelwida; Berliana, Berliana (Jurnal Agripet, 2024)
This study aimed to assess the chemical quality (moisture content, protein, and fiber) and organoleptic properties of chicken nuggets with the addition of vegetables. The materials used included chicken breast, wheat flour, tapioca flour, bread crumbs, eggs, pepper, salt, ice water, carrots, broccoli, spinach, and young corn. Five treatments were applied: P0 (no vegetable addition), P1 (carrot addition), P2 (broccoli addition), P3 (spinach addition), and P4 (young corn addition). The research employed a Completely Randomized Design (CRD) for analyzing chemical quality and a Randomized Block Design (RBD) for examining organoleptic properties. Preferences were tested using the Kruskal-Wallis test. The chemical quality measurements included moisture content, protein, and crude fiber, while the organoleptic measurements assessed color, aroma, texture, taste, and preference. The results showed that the addition of vegetables significantly (P0.05) affected moisture content but had no significant effect (P0.05) on protein and fiber content. Furthermore, the addition of vegetables significantly (P0.05) influenced the color, aroma, and taste of the nuggets, but did not significantly affect (P0.05) texture and preference. It was concluded that incorporating 10% vegetables into chicken nuggets increased moisture content without affecting protein and fiber levels or overall preference. The addition of carrots yielded the highest scores for aroma and taste preference.